2002
DOI: 10.1007/s101030200029
|View full text |Cite
|
Sign up to set email alerts
|

Er:YAG Laser Modification of Root Canal Dentine: Influence of Pulse Duration, Repetitive Irradiation and Water Spray

Abstract: The aim of this study was to determine the effects of varying parameters of Er:YAG laser irradiation with and without water spray cooling on root canal dentine in vitro. After horizontally removing tooth crowns from extracted human teeth, roots were axially sectioned into thin slices, exposing the root canal surface. An Er:YAG laser delivered 10-30 J/cm(2) into a 0.4-mm diameter laser spot on the root canal surface. Single pulses of different lengths (80-280 micro s) were applied with and without water spray c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
1
19
0
3
Order By: Relevance
“…To date, few researchers have examined the effects arising from varied pulse durations of Er: YAG laser [20][21][22][23] . With varied laser pulse durations and energy fluences of Er: YAG laser, Majaron et al 21) quantitatively examined their effects on depth and diameter and calculated the crater volumes thereof.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To date, few researchers have examined the effects arising from varied pulse durations of Er: YAG laser [20][21][22][23] . With varied laser pulse durations and energy fluences of Er: YAG laser, Majaron et al 21) quantitatively examined their effects on depth and diameter and calculated the crater volumes thereof.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the different results could be caused by the thermal effect arising from 10 consecutive laser pulse irradiations without water spray cooling. Ebihara et al 20) reported that an Er: YAG laser with 80-μs pulse duration featured a deeper ablation effect than 180 and 280 μs at 20 J/cm 2 . The main purpose of their study 20) was to determine the surface and subsurface modifications of root canal dentin after Er: YAG laser irradiation under variable conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations